Linguagem e psicanálise: a incidência do sujeito do inconsciente na escrita e na leitura inicial da criança. - Carvalho, Magda Wacemberg Pereira Lima (2020)
Understanding that the interaction with texts provided by the other (alterity) allows the appearance of graphic-textual aspects in the child’s nascent writing and understanding that the access to writing implies that one transits through the representations of the Other (radical alterity), the present work has the aim to investigate evidence of the unconscious formations in the writing and reading of children in written language acquisition. For this, the study is based on interactionism in language acquisition, which is based on structuralist linguistics with a European dimension and Lacanian psychoanalysis. We assume that traces of experiences lived by the child when repressed, they will return in what is recorded on the sheet of paper and, also, in the reading that the child makes of his written productions. Because what erupts in children’s early reading and writing results as much from the child’s changing position in language as from the manifestation of features of the unconscious. Through this understanding, we chose to investigate writing and reading activities performed in the classroom by children that are three and five years old, enrolled in the first, second and third level of kindergarten of the Basic Education private School of the Serra Talhada/PE. Regarding the methodological aspects of the research, we opted for a qualitative approach to the case study and the data collection included direct observation, participant observation and video recording of writing and reading activities. The results showed that, at the beginning of their journey through the written language, the child writes heterogeneous graphic forms, read as texts of the constituted written language, which allowed us to observe that reality data were transformed into signifiers that, in a metaphorical slip and metonymic, were replaced and/or shifted to the signifiers manifested in the child’s writing and reading, which may indicate evidence of the subject’s presence in the unconscious.